The role of politics in the allocation of multilateral aid - Hernández, Diego (2015)
This dissertation studies the role of politics in the conformation of IFIs. Each of its three chapters explores the rootedness of politics in every key component of IFIs: mission, structure, and policy. Chapter 1 takes the mission of the IFI as a starting point to understand the diffusion of political favoritism in its lending decisions. The foundation of IFIs often responds to the desire of the main sponsor to spread its area of influence and this is reflected in the mission. Here, the Islamic Development Bank (IsDB) is taken as an example. The IsDB is an RDB initiated with the support of King Faisal Bin Abdulaziz of Saudi Arabia and restricted to countries with significant Muslim populations. The analysis explores to what extent IsDB lending follows the interests of Saudi Arabia in the Islamic world based on religious affinity. Chapter 2 focuses on the structure of IFIs as facilitators of political favors. The number of voting shares is generally assigned to each member according to their capital contributions and it is the most important feature in the structure of IFIs because it provides institutional control to large stakeholders. This chapter considers the Inter-American Development Bank (IDB) to identify the effect of the preference heterogeneity of influential members on the ease of approving politically motivated loans. And lastly, chapter 3 observes how IFIs adjust their policies to cope with the conflicting interests of other actors. Credit conditionality is the main policy instrument of IFIs to improve aid effectiveness but it can also serve to maintain an area of influence. Donors can engage in a “race to the bottom" through credit conditionality to reach borrowers and achieve influence over them. This chapter investigates the extent to which World Bank conditionality responds to the rising presence of “new” donors in Africa. The three chapters provide evidence on the three core arguments supporting the claim that IFIs are failing to promote growth. Namely, they are in the first place not necessarily founded to promote growth, their structures are designed to allow their main donors to control them, and their policies are inconsistent and can be designed to protect their self-interests. The dissertation also suggests what to expect from IFIs in the near future and highlights the key areas that need to be reformed to hinder politically motivated lending.